18th IEEE Computer Security Foundations Workshop (CSFW'05)
DOI: 10.1109/csfw.2005.10
|View full text |Cite
|
Sign up to set email alerts
|

Belief in Information Flow

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
121
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(125 citation statements)
references
References 19 publications
2
121
0
Order By: Relevance
“…Clarkson et al [21,22] showed that the Shannon entropy approach is inadequate for measuring information flow when the adversary makes assumptions about the high-level secret and such assumptions might be incorrect. Based on the conviction that it is unavoidable that the attacker makes such (potentially inaccurate) assumptions, they proposed a new metric.…”
Section: Belief Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Clarkson et al [21,22] showed that the Shannon entropy approach is inadequate for measuring information flow when the adversary makes assumptions about the high-level secret and such assumptions might be incorrect. Based on the conviction that it is unavoidable that the attacker makes such (potentially inaccurate) assumptions, they proposed a new metric.…”
Section: Belief Approachmentioning
confidence: 99%
“…As far as we know, [21,22] have been the first papers to address the adversary's beliefs in quantifying information flow. This line of work, which inspired our formulation of the belief-vulnerability, is based on the KullbackLeibler distance, a concept related to Shannon entropy which in general, as already mentioned in Section 3, fails to characterize many realistic attacks scenarios.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Papers with a foundational focus include those of Clarkson et al (2005), Köpf and Basin (2007), Malacaria (2007), Chatzikokolakis et al (2008), Smith (2009), McIver et al (2010, Barthe and Köpf (2011) and Alvim et al (2012). Andrés et al (2010) and Heusser and Malacaria (2010).…”
mentioning
confidence: 99%
“…While the leakage should depend on the difference induced by the belief change due to the observation, the averaging probability should remain the same. (A similar concern has also inspired the works of [5] and [7].) In order to avoid the unnatural consequence of a negative leakage, we propose to base the notion of leakage directly on the (more primitive) notion of mutual information.…”
mentioning
confidence: 99%